LANGGHAR, KOPHUNG DAN BHAQAF Konservasi Kebudayaan Khazanah Keislaman Madura - Mohsi Mohsi (Fakultas Ilmu Budaya Universitas Diponegoro, 2019)
Langghar, Kophung and Bhaqaf in Madurese society exist as a distinctive cultural entity, whose uniqueness is continually contributing to the cultural treasures of the past. Langghar, Kophung and Bhaqaf are a distinctive Madurese culture that has never been lost by the gradation of the age, and the change of time. Their existence serves as a form and effect of conservation and the expression of the strength of the Madurese community in preserving the culture of their ancestors. The existence of langghar, kophung and bhaqaf can be a very important part of the culture for the Madurese community, especially in terms of ethical values, religious values, and philosophical values that are found in them. These values continue to be searched more intensely, in an effort to uncover the sacredness and uniqueness that are still neatly stored. One of the values which continues to be respected in langghar, kophung and bhaqaf is the value of religiosity which has never been dispirited up to the present.